The Effectivenss Of Teams Games Tournament Model To The 5th Grade Students’ Learning Outcomes On Social Science - Istiqomah, Isa Ansori, Istiqomah (Universitas Negeri Semarang, 2017)
This research’s background is the problem in the low number of learning outcomes in the social studies subject of 5th GRADE students of SDN Gugus Melati Semarang. The purpose of this study is to test whether or not the TGT learning model is effective on the learning outcomes of 5th GRADE students of SDN Gugus Melati Semarang on social science subject. This research is an experimental research with quasi experiment design in the form of nonequivalent control group design. The population of this study is the students of grade 5 at SDN Gugus Melati Semarang. The technique used in data analysis are normality test, homogeneity test, equality test average, hypothesis test, and n gain test. The result of hypothesis test shows that tcount is 7,104 while ttable value with dr = 67 is 1,996. The data indicates that tcount > ttable then Ha is accepted. The conclusion of this research is the TGT model is effective to the learning outcomes on social science subject of 5th GRADE students of SDN Gugus Melati Semarang.